Identification of a novel splice variant for mouse and human interleukin-5. Issue 3 (March 2020) - Shilovskiy, Igor; Andreev, Sergei; Mazurov, Dmitriy; Barvinskaia, Ekaterina; Bolotova, Svetlana; Nikolskii, Alexander; Sergeev, Ilya; Maerle, Artem; Kudlay, Dmitrii; Khaitov, Musa
Abstract: Expression of interleukins and their receptors is often regulated by alternative splicing. Alternative isoform of IL-5 receptor α-chain is well studied; however, no data on functional alternative splice variants of IL-5 has been reported up today. In the present study, we describe a novel splice variant for the mouse and human IL-5. The new form was found during analysis of PCR-products amplified from different mouse lymphoid tissues with a pair of primers designed to clone full-length mIL-5 ORF. A single short isoform of mIL-5 was detected along with the canonical full-length mRNA in ConA-stimulated lymphoid cells isolated from spleen, thymus, lymph nodes and blood. It was 30–40 nt shorter, and less abundant than classical form. The sequence analysis of an additional form of mIL-5 revealed that it lacks exon-2 (δ2). Using RT-PCR with the splice-specific primers we obtained an additional evidence for δ2 form expression. To verify whether mIL-5δ2 transcript is translated into protein, the coding sequences corresponding to full and δ2 forms of mIL-5 were cloned into an expression plasmid. After transfection into the human 293T cell line, we found that the short form of mIL-5 protein is expressed in cells and secreted into the supernatant, but at the reduced level than that detected for full isoform of mIL-5. Fluorescence microscopy examination revealed a partial translocation of mIL-5δ2 into cytoplasm, whereas mIL-5 resided mostly within endoplasmic reticulum. This can explain why the level of δ2 protein expression was reduced. Using a similar set of experimental approaches, we received the evidence that the human IL-5 mRNA has the δ2 splice form (hIL-5δ2) as well. It can be firmly detected by RT-PCR in PHA-activated mononuclear cells isolated from peripheral blood of healthy persons or patients with asthma. Altogether, our results showed that the human and mouse IL-5 have an alternative mRNA splice isoform, which loses exon-2, but nevertheless is expressed at protein level. However, more comprehensive studies will be required for evaluation of IL-5δ2 expression, regulation, biological function and clinical significance. Abstract : Immunology; Genetics; Gene expression; Biomolecules; Cytokine; Lymphocytes; Alternative splicing; Protein expression